2019
DOI: 10.1016/j.jaci.2018.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Nasal allergen-neutralizing IgG4 antibodies block IgE-mediated responses: Novel biomarker of subcutaneous grass pollen immunotherapy

Abstract: Background: Grass pollen subcutaneous immunotherapy (SCIT) is associated with induction of serum IgG 4-associated inhibitory antibodies that prevent IgE-facilitated allergen binding to B cells. Objective: We sought to determine whether SCIT induces nasal allergen-specific IgG 4 antibodies with inhibitory activity that correlates closely with clinical response. Methods: In a cross-sectional controlled study, nasal fluid and sera were collected during the grass pollen season from 10 SCIT-treated patients, 13 unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
81
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 35 publications
(50 reference statements)
9
81
0
2
Order By: Relevance
“…17,26,27 IgG 4 depletion results in the recovery of allergen-IgE binding to B cells. 26,32 In this study we also observed the regulatory role of IgG antibody in nasal polyp homogenates of patients with CRSwNP. IgG-regulated FcεRII (CD23) mediated IgE-facilitated allergen presentation by B to T cells.…”
Section: Discussionsupporting
confidence: 59%
“…17,26,27 IgG 4 depletion results in the recovery of allergen-IgE binding to B cells. 26,32 In this study we also observed the regulatory role of IgG antibody in nasal polyp homogenates of patients with CRSwNP. IgG-regulated FcεRII (CD23) mediated IgE-facilitated allergen presentation by B to T cells.…”
Section: Discussionsupporting
confidence: 59%
“…Allergen specific IgG4s are bispecific antibodies that may block antigenic epitopes and act as blocking antibodies and it may be responsible for postimmunotherapy serum inhibitory for IgE [12]. By ELIFAB, it was found that serum inhibitory activity for IgE increased significantly after SCIT (P < 0.05) and correlated moderately with levels Table 2 Sensitization of AR-sIgG4 (r = − 0.501,P < 0.01), as in former studies [10,11]. However, there is no significant relationship between serum inhibitory activity for IgE and clinical improvements, which is different from what have been reported.…”
Section: Discussionsupporting
confidence: 58%
“…As a part of it, the inhibition of binding of IgE-allergen complexes to B cells can be tested by the IgE-FAB assay [9]. It has been demonstrated that the serum inhibitory activity for IgE, determined by the IgE-FAB assay, increased after AIT and had relevance with the clinical improvements [10,11]. Moreover, it has been recommended as potential biomarker for efficacy of AIT in 2017 EAACI Position Paper [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Moreover, nasal specific IgE (N-sIgE) has been proposed as a control parameter for the efficacy of allergen-specific immunotherapy (AIT). [17][18][19] IgE testing in NS has been also suggested as a potentially beneficial non-invasive tool to identify the local onset of IgE production in small children. 20,21 Many efforts have been made to standardize the methodology of NS collection.…”
Section: Introductionmentioning
confidence: 99%